(untitled) (UNED Research Journal, 2022)
Introduction: On January 8, 2009, Costa Rica was hit by the Cinchona earthquake in Alajuela Province. When the earthquake hit, a network of automatic cameras had been operating in the premontane rain forest for two years, recording the relative abundance of mammals. Objective: To quantify the relative abundance of wild mammals in the Cinchona area, before the earthquake, and to serve as a point of comparison for future studies. Methods: With automatic cameras running a total of 1555 "camera-nights". Results: I obtained 150 photographs corresponding to 10 species. The most abundant were the peccary, Pecari tajacu, with 150 records; the guatuza, Dasyprocta punctata, with 31; and the tepezcuintle, Cuniculus paca, with 29 records. I also recorded the puma, Puma concolor (one male and one female, 0,02 pumas/km2); and the ocelot, Leopardus pardalis (one male, two females and one calf, 0,43ind/km2). Conclusion: The abundance of wild mammals in Cinchona was relatively low before the earthquake, but it included large cats declared endangered in Costa Rica.